Davis, Vee (London, 2013)
2013 "Davis, Vee", 2013, HistoryTalk Velma Vee Davis was born and brought up in Trinidad. She arrived in Notting Hill in 1957, the year before the race riots, and became a Rachman tenant in Powis Square. She rebuffed an attempt by Michael de Freitas (aka Michael X) to be her pimp, and worked at Osram light-bulb factory in Hammersmith, scything leather in Shepherds Bush, and as a nurse in London, Canada and America. Recently she has started a new career as a model/actress, appearing in Vogue magazine, an advert with Billy Connolly, a Harry Potter film, Love Actually, and Alicia Keys Girl On Fire video. Vee has also run a stall at Notting Hill Carnival for many years and worked as a chef for Richard Branson at the Virgin Manor studios in Oxfordshire.